2020
DOI: 10.1007/s00405-020-06421-w
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral ultrasonography in the assessment of DOI in oral cavity squamous cell carcinoma: a comparison with magnetic resonance and histopathology

Abstract: Objective The first-line therapeutic approach for oral cavity squamous cell carcinoma (OCSCC) is complete surgical resection. Preoperative assessment of depth of invasion (cDOI) is crucial to plan the surgery. Magnetic resonance (MR) and intraoral ultrasonography (IOUS) have been shown to be useful tools for assessment of DOI. The present analysis investigates the accuracy of MR and IOUS in evaluating DOI in OCSCC compared to histological evaluation (pDOI). Materials and methods Forty-nine previously untreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 37 publications
0
39
2
Order By: Relevance
“…Therefore, in this study, the accuracy of diagnostic imaging was estimated by comparing the DOI measured by CT, MRI, and US with the DOI measured histopathologically in the same target group. Few studies have evaluated primary lesions of tongue cancer by CT [ 14 , 15 , 31 ]. Although CT has better spatial resolution than MRI, metal artifacts often make it difficult to evaluate lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in this study, the accuracy of diagnostic imaging was estimated by comparing the DOI measured by CT, MRI, and US with the DOI measured histopathologically in the same target group. Few studies have evaluated primary lesions of tongue cancer by CT [ 14 , 15 , 31 ]. Although CT has better spatial resolution than MRI, metal artifacts often make it difficult to evaluate lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This was likely one of the factors that made the 95% limit of agreement in the Bland–Altman analysis larger than that of MRI. Previous reports have suggested that CT is accurate enough to assess the primary lesion of tongue cancer [ 14 , 15 , 31 ], and this effect should also be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Filauro et al. ( 28 ) also noted that the mean difference between sonographic DOI and histologic DOI was only 0.3 mm after analyzing the outcome of 49 patients with cT1-3 tongue SCC, and the two DOIs were significantly related. Together with our results, these findings indicate the high reliability and accuracy of DOI evaluation by ultrasound even in cT1 tumors.…”
Section: Discussionmentioning
confidence: 96%
“…[19][20][21][22][23] Conventional ultrasonography (US) has been previously employed for the evaluation of maxillofacial diseases, in particular for the preoperative assessment of malignant lesions. [24][25][26][27][28][29] Ultra-high frequency ultrasound (UHFUS) represents an emerging technique for the diagnosis of several pathologic conditions affecting the oral mucosa. UHFUS is characterized by the use of US frequencies in the range between 30 and 100 MHz, providing high-resolution imaging of superficial layers.…”
Section: Introductionmentioning
confidence: 99%